1998
DOI: 10.1142/s0217751x98000305
|View full text |Cite
|
Sign up to set email alerts
|

On the Geometrization of Bohmian Mechanics: A New Approach to Quantum Gravity

Abstract: In this paper, a new approach to quantum gravity is presented in which the de-Broglie–Bohm quantum theory of motion is geometrized. This way of considering quantum gravity leads automatically to the fact that the quantum effects are contained in the conformal degree of freedom of the space–time metric. The present theory is then applied to the maximally symmetric space–time of cosmology, and it is observed that it is possible to avoid the initial singularity, while at large times the correct classical limit em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(101 citation statements)
references
References 5 publications
2
99
0
Order By: Relevance
“…In a previous paper [1] it was shown that the application of an idea of de-Broglie leads to the fact that the quantum effects of matter are equivalent to a specific conformal factor of the space-time metric. In the de-Broglie-Bohm relativistic quantum theory [3], the Klein-Gordon equation…”
Section: Quantum Effects Scale and Conformal Transformationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous paper [1] it was shown that the application of an idea of de-Broglie leads to the fact that the quantum effects of matter are equivalent to a specific conformal factor of the space-time metric. In the de-Broglie-Bohm relativistic quantum theory [3], the Klein-Gordon equation…”
Section: Quantum Effects Scale and Conformal Transformationsmentioning
confidence: 99%
“…This new metric is called the physical metric because it has physical interpretation. For example the singularities of FRW universe would be removed in g µν [1].…”
Section: Qmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, as was already shown by Shojai et al in [3], the quantum potential modifies the background geometry giving a curved space-time with the metric given by eq. (13).…”
Section: Epr Correlations Via a Wormholementioning
confidence: 59%